Modern Apitherapy in the Treatment of Lyme Arthritis - Matsko, Nataliia; Pokhmurska-Hudym, Nataliia; Ambrozevych, Zoryana; Tolopko, Solomiia; Ferko, Mariia (SSP Modern Pharmacy and Medicine, 2025)
Today there is a danger of spreading Ixodes ticks, which can cause Lyme disease, which is characterized by polysystemic lesions. As a rule, treatment involves antibiotic therapy. We studied the effectiveness of apitherapy by bee sting method in the complex treatment of patients with Lyme arthritis. Patients were prescribed a course of bee stings from 1 to 15 bee stings once every other day, a total of 102 stings. After a course of apitherapy, patients had significantly reduced or eliminated pain in the spine and joints, there was a significant decrease in IgM during bee stings between courses of antibiotic therapy and IgG in tests performed after a course of treatment with bees. Apitherapy can have a pronounced antibacterial effect over the next 2 years. In addition to these findings, further observations indicated that the immunomodulatory effects of bee venom may play a crucial role in mitigating inflammatory responses. Patients not only experienced relief from pain but also reported improved mobility and overall quality of life. The gradual reduction in specific antibody levels suggests that the bee sting treatment may help recalibrate the immune system over time. This additional benefit, coupled with the direct antibacterial properties of the venom, positions apitherapy as a promising complementary treatment approach. Continued research into the long-term effects is warranted to better understand its full therapeutic potential. Moreover, the observed improvements were supported by both subjective patient reports and objective clinical measurements. The treatment appeared to modulate the inflammatory cascade associated with Lyme arthritis, leading to fewer flare-ups and a reduction in joint stiffness. This innovative method also showed potential in preventing further joint degradation, thereby extending its benefit beyond immediate pain relief. Future studies are needed to explore the optimal dosing, frequency, and possible synergies with conventional antibiotic therapies, ensuring that patients receive the most effective comprehensive care.